Pengaruh Produk, Influencer dan Strategi Promosi Media Sosial Terhadap Keputusan Pembelian Herborist - Ginanjar Rahmawan; Dewi Setyorini (Universitas Mercu Buana, 2021)
The research was intendeed to analyze and test the impact of products, Influencer and strategy of social media promotion on Herborist decision purchase.The expected objectives of this research are (1) to find how products, influencer and social media promotions and purchasing decisions (2) to identify the impact of products, influencers, and social media promotion are both partial and simulational to decision of the purchase. The method of data collection used in the research uses an online questionnaire handed out to 77 female responden at 18-32 years old in Surakarta which have used Herborist product. The method of data analyze uses lihe result have shown that products, Influencer, and sosial media promotions strategy significantly affect Herborist purchase decisions. Keywords : product, influencer, promotion, social media, purchase decision